2014
DOI: 10.1371/journal.pone.0111657
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Image-Guided Biopsy for Non-Mass-Forming Isolated Splenomegaly and Suspected Malignant Lymphoma

Abstract: BackgroundThe aim of this study was to evaluate the accuracy, safety, and role of splenic biopsy in the management of patients with non-mass-forming isolated splenomegaly and suspected malignant lymphoma.MethodsBetween 2001 and 2013, 137 biopsies were performed under computed tomography (CT) fluoroscopic guidance in 39 patients. All patients had splenomegaly based on the CT findings and a suspected diagnosis of malignant lymphoma based on their clinical symptoms. The spleen was the only accessible site to perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…In cases of isolated splenomegaly, detailed history, examination and appropriate investigations are essential to exclude a systemic illness 2. The most common causes of isolated splenomegaly are haematological: 25–66%, hepatic: 12–46%, infective: 13–25%, primary splenic: 25% and others: 8–21% 1…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In cases of isolated splenomegaly, detailed history, examination and appropriate investigations are essential to exclude a systemic illness 2. The most common causes of isolated splenomegaly are haematological: 25–66%, hepatic: 12–46%, infective: 13–25%, primary splenic: 25% and others: 8–21% 1…”
Section: Discussionmentioning
confidence: 99%
“…The spleen is a common site of lymphoma dissemination and may be involved with any lymphoid malignancy. However, primary splenic lymphoma represents a rare diagnosis 2. According to some authors it accounts for <1% of incidences, as it is strictly defined by involvement of only the spleen and splenic hilar lymph nodes, in the absence of any other localised tumours 7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in a study completed after the meta-analysis, which looked at 137 patients with isolated splenomegaly undergoing CTguided fine-needle biopsy, Tokue et al reported only three adverse events 4 . This study is particularly valuable because it may be more relevant to modern biopsy techniques, helping to confirm the results from the meta-analysis and older studies 1,5 .…”
Section: Literature Reviewmentioning
confidence: 99%